Development and Experimental Study of Emergency Power Pack for Fisherman - Abd Rashid, Wan Norhisyam; Kadmin, Ahmad Fauzan; A Subki, A Shamsul Rahimi; Ab Hadi, Nik Azran; Saat, Shahrizal; Tumari, Mohd Zaidi; Rahim, Norain (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Imagine that we stuck in the middle of nowhere after the engine of our boat break down and we have nothing to depend on. Portable power pack will energise our appliances such as radio, cell phone, portable fans and the most important things, the emergency light. We can have the same experience that we have at home while going out on a fishing trip when we bring along a backup power source such as portable power pack. In this project, a portable power pack has been developed purposely for fisherman. This portable power pack is equipped with two power generators namely solar power and small turbine power. These generators will charge the portable power pack accordingly. An emergency switch is prepared for us to send the SOS message via SMS and send our location via GPS device. This will give the opportunity for the rescue team to find our location easily when anything goes wrong. Experimental studies have been done to evaluate the performance of the developed power pack.